Management of Headache and Headache Medications - Robbins, Lawrence D. (Springer US, 1994)
This is a comprehensive, cohesive, and state-of-the-art book for very practical management of headache patients. Headache types are divided into simple, practical categories, giving the reader a "user-friendly" step-by-step guide to diagnosis, treatment, and management of all types of headache. In-depth treatment, featuring first, second and third line abortive and preventive medication, is presented for migraine, chronic daily, and cluster headache. Also featured are extensive sections on hormonal aspects of headache, headache in children, as well as such important topics as posttraumatic headache, lumbar puncture headache, indomethacin response syndromes, and occipital neuralgia. Useful case histories are presented along with illustrative "Quick Reference Guides" prior to each major section. Non-medicine strategies are discussed, including diet and relaxation techniques. For all general practitioners, neurologists, and residents, this book presents the most thorough and practical treatise on headache management.